Insights into Self-Knowledge from Islamic Teachings: A Path Towards Ethical Environmental Stewardship within the Framework of the SDGs - Ahmad Abedi Sarvestani (Profetika: Jurnal Studi Islam, 2024)
Objective: This study explores the significance of self-knowledge derived from Islamic teachings as a foundation for ethical environmental stewardship within the framework of the Sustainable Development Goals (SDGs). The research aims to bridge the gap between spiritual awareness and sustainable environmental practices, emphasizing the need for integrating Quranic principles into contemporary ecological discourses. Theoretical framework: The theoretical framework is grounded in the Quranic understanding of human nature, which balances spiritual and material dimensions. Literature Review: Key literature highlights the role of Islamic values, such as justice (adl), mercy (rahmah), and stewardship (khilafah), in shaping responsible environmental behaviors. Methods: Using a qualitative approach, the study employs textual analysis of Quranic verses and Hadith, complemented by a review of contemporary scholarly works on Islamic ethics and environmental sustainability. Results: The findings reveal that self-knowledge, encompassing awareness of one's divine purpose and responsibilities, is pivotal in fostering ethical interactions with nature. The research highlights that when materialistic tendencies dominate, they lead to the overexploitation of natural resources. Conversely, nurturing divine attributes promotes practices that align with the goals of environmental conservation and sustainability as envisioned in the SDGs, particularly Goals 12 (Responsible Consumption and Production), 13 (Climate Action), and 15 (Life on Land). Implications: The study contributes to the growing discourse on the integration of religious values into global sustainability efforts, presenting a novel perspective on how self-awareness can influence environmental ethics. Its implications are significant for policymakers, educators, and faith-based organizations, offering a framework to inspire community-driven environmental initiatives rooted in Islamic teachings. Novelty: The novelty of this research lies in its intersectional approach, combining Islamic epistemology, ethical philosophy, and sustainability science to address global environmental challenges. By aligning individual actions with divine principles, the study provides a transformative model for achieving ethical and sustainable development.